EFFECTIVENESS OF JASMINE OIL (JASMINUM OFFICINALE) MASSAGE ON REDUCTION OF LABOR PAIN AMONG PRIMIGRAVIDA MOTHERS - Hamid Mukhlis; Nurhayati Nurhayati; Riska Wandini (Malahayati International Journal of Nursing and Health Science, 2019)
Background: Intolerable labor pain encourages maternal use of painkillers such as analgesics and sedatives while these drugs have side effects on the mother and fetus.Methods: Quantitative research by using a quasi-experimental approach with one group pretest posttest. The population in this study was maternity during the phase I active with sample  was 20 respondents. The study conducted on March 2018 at Teluk Pandan, Pesawaran, Lampung-Indonesia.Results: The Effectiveness of counter pressure massage using jasmine oil (jasminum officinale) in reducing delivery pain with p-value 0,000Discussion: The positively significant alteration in delivery pain score after therapySuggestions: That therapy could be alternative to help in reducing delivery pain.